1979
DOI: 10.1177/009539977901100301
|View full text |Cite
|
Sign up to set email alerts
|

Organization Setsize and Diversity

Abstract: This study investigates the interorganizational linkages ofpeople-processrng organizations. Specifically, the determinants of the size and diversity of their organization sets are examined. Predictors are grouped according to the amount of discretion local agency directors have to manipulate them. It is shown that the best predictors of organization set size and composition are variables over which local adminrstrators have little control. The implications of this finding for the design of social service deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Likewise, Schermerhorn and Shirland (1981) found that the perceived availability of cooperative partners predicted hospitals' arrangements for shared ancillary (although not medical) services. Finally, although Whetten and Aldrich (1979) did not find manpower agencies' staff professional activity to be associated with IORs, staff memberships in local voluntary organizations did predict such ties. On balance, then, it appears that staff members' external activities can facilitate entry into IORs.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…Likewise, Schermerhorn and Shirland (1981) found that the perceived availability of cooperative partners predicted hospitals' arrangements for shared ancillary (although not medical) services. Finally, although Whetten and Aldrich (1979) did not find manpower agencies' staff professional activity to be associated with IORs, staff memberships in local voluntary organizations did predict such ties. On balance, then, it appears that staff members' external activities can facilitate entry into IORs.…”
mentioning
confidence: 62%
“…Some studies have supported the view that the social status of agency staff will affect IORs (Paulson 1976;Eisenhardt and Schoonhoven 1996). In the previously cited study of manpower organizations, however, staff members' professional training was not associated with IORs (Whetten and Aldrich 1979). Whetten and Aldrich's study is arguably the most relevant to drug abuse treatment centers because manpower agencies are also ''people processing organizations'' (p. 252) whose production function consists of changing people and then facilitating their placement within the community.…”
Section: Opportunities To Cooperatementioning
confidence: 96%
See 3 more Smart Citations